2016
DOI: 10.1021/acssuschemeng.5b00774
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Levulinic Acid to γ-Valerolactone in Water Using Millimeter Sized Supported Ru Catalysts in a Packed Bed Reactor

Abstract: γ-Valerolactone (GVL) has been identified as a sustainable platform chemical for the production of carbon-based chemicals. We here report an experimental study on the catalytic hydrogenation of levulinic acid (LA) in water to GVL in a packed bed reactor using supported Ru catalysts (carbon, alumina, and titania) with particle sizes in the millimeter range (C LA,0 = 1.2 mol/L, LA feed = 1 mL/min, H 2 feed = 30 mL/min, 90 °C, 45 bar, and WHSV = 30 g feed /g cat •h). Intraparticle diffusion limitations for hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 45 publications
1
68
0
Order By: Relevance
“…The decrease in activity after the fourth recycle is due the formation of small amount of coke on the catalyst (0.38% of carbon deposition on catalyst after the fourth recycle, confirmed from CHNS analysis). The comparison study of activity results of our catalyst with other reported catalysts was reported in the Table S1 ,…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in activity after the fourth recycle is due the formation of small amount of coke on the catalyst (0.38% of carbon deposition on catalyst after the fourth recycle, confirmed from CHNS analysis). The comparison study of activity results of our catalyst with other reported catalysts was reported in the Table S1 ,…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the reaction products from LA hydrogenation in water The composition of the aqueous reaction mixtures (LA, 4-HPA and GVL) was determined quantitatively by 1 H NMR. NMR analysis proved to be the most reliable method for the quantification of 4-HPA, which is difficult to determine by GC or HPLC [35]. A sample (approximately 200 μL) was weighed, dissolved in D 2 O and dioxane (internal standard, 10 μL) was added.…”
Section: Catalytic Hydrogenation Of Lamentioning
confidence: 99%
“…Besides variations in support phase composition, many different synthetic procedures for titania-supported Ru catalyst preparation have been reported varying in the choice of, e.g., metal precursor, impregnation method and activation procedure (Table 1), which all may affect catalyst performance. Wet impregnation is most commonly used method for the synthesis of these Ru/TiO 2 catalysts [19,20,25,29], using Ru precursors such as RuCl 3 , Ru(NO)(NO 3 ) 3 , Ru(acac) 3 , Ru (NH 3 ) 6 Cl 3 or Ru 3 (CO) 12 [19,20,25,[29][30][31][32][33][34][35]. Limited information is available on the effects of these synthesis parameters on LA hydrogenation activity for Ru/TiO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[41] However,m ost reported studies were performed under batch conditions, ando nly af ew of them were under flow conditions for the hydrogenation of LA instead of alkyl levulinates. [42][43][44][45][46][47] Considering the advantageso ff low reactions (efficient energy utilization,e asy scale-up, purification, etc. ), this technique could provide ac loser insight into practical production in industry by mimicking large-scale production on the laboratory scale.…”
Section: Introductionmentioning
confidence: 99%